Implementasi Moderasi Beragama dalam Meningkatkan Kerukunan Suku Anak Dalam di Desa Dwi Karya Bakti Jambi - Asniah, Asniah; Rosyad, Rifki (Refleksi, 2023)
This study aims to explore and analyze the implementation of religious moderation in improving interreligious harmony among Suku Anak Dalam in Dwi Karya Bakti Village, Jambi Province. Suku Anak Dalam is a community that coexists with members who adhere to Hinduism, Buddhism, Christianity, animism, and Islam. Despite their religious diversity, they still live peacefully and harmoniously. The results showed that implementing religious moderation among the Suku Anak Dalam in Dwi Karya Bakti Village had a positive impact. The Suku Anak Dalam community daily exhibits tolerance, mutual respect, and inter-religious cooperation. Interfaith dialogue activities, inclusive religious rituals, and cooperation in socio-religious activities are concrete examples of successful implementation of religious moderation. However, this study also identifies several challenges in implementing religious moderation in the Suku Anak Dalam. Factors such as limited access to formal education, infrastructure constraints, and geographical differences are obstacles to widely spreading the understanding of religious moderation in this community.